Proceso atención de enfermería en paciente adulto mayor con absceso hepático amebiano. - Pinos Ramírez, Jonathan Joffre (2021)
The present clinical case was performed on an adult patient over 64 years of age who has been admitted to the Dr. José Cevallos Ruiz Basic Hospital (Yaguachi) through the emergency area, presenting with colicky abdominal pain of moderate intensity in the right upper quadrant. one month of evolution, apparent cause of eating food stored for days from its preparation, accompanied by hyporexia, dysentery for more than 5 days, emesis, anorexia, weight loss, asthenia and abdominal distension. In laboratory test results, Entamoeba Histolytica Cyst (+++) is observed, in abdominal ultrasound an amoebic liver abscess located in the left lobe with 5.8cm is observed, which distinguishes a focal lesion, a round one measuring 29cm in diameter. He does not present a personal, family, allergic or surgical pathological history. A nursing care plan is drawn up, achieving favorable results that helped improve the health and condition of the patient during their stay in the health unit.